The Use of Mnemonic Method and Its Implications for Arabic Learning - Sholiha, Amila; Aisyahrani, Asa Ismia Bunga (Universitas Yudharta Pasuruan, 2023)
Success in learning Arabic can be influenced by the selection of the right method by the teacher during learning. The method used in the learning process is often in the spotlight. This study aims to discuss the use of the mnemonic method and its realization in learning Arabic. This research uses a literature study with a descriptive qualitative approach. Data obtained from observation and analysis of books and scientific articles related to the use of the mnemonic method. While the data were analyzed in descriptive-analytical, including data reduction, data presentation, and conclusion. The results of this study indicate that the use of the mnemonic method helps students in their ability to remember the new vocabulary, grammar, and Arabic rules they have learned. The material is stored in students' memories for a long time.